Characterization of two human induced pluripotent stem cell lines derived from Batten disease patient fibroblasts harbouring CLN5 mutations - Marisa Ofrim; Daniel Little; Mina Nazari; Christopher J. Minnis; Michael J. Devine; Sara E. Mole; Paul Gissen; Maëlle Lorvellec (Stem Cell Research, 2024)
The neuronal ceroid lipofuscinoses (NCLs) are a group of common inherited neurodegenerative disorders of childhood. All forms of NCLs are life-limiting with no curative treatments. Most of the 13 NCL genes encode proteins residing in endolysosomal pathways, such as CLN5, a potential lysosomal enzyme. Two induced pluripotent stem cell lines (hiPSCs) were generated from skin fibroblasts of CLN5 disease patients via non-integrating Sendai virus reprogramming. They demonstrate typical stem cell morphology, express pluripotency markers, exhibit trilineage differentiation potential and also successfully differentiate into neurons. These hiPSCs represent a potential resource to model CLN5 disease in a human context and investigate potential therapies.